2001
DOI: 10.1002/1097-4644(20010401)81:1<114::aid-jcb1028>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

A synthetic heparin-mimicking polyanionic compound binds to the LDL receptor-related protein and inhibits vascular smooth muscle cell proliferation

Abstract: A synthetic heparin-mimicking polyaromatic anionic compound RG-13577 (polymer of 4-hydroxyphenoxy acetic acid and formaldehyde ammonium salt, Mr approximately 5800) exhibits specific binding to vascular smooth muscle cells (SMCs) and inhibits their proliferative response to growth promoting factors. Receptor binding of (14)C-RG-13577 was efficiently competed by apolipoprotein E3 (apoE), lactoferrin, and the LRP (LDL receptor-related protein) receptor associated 39 kDa protein (RAP). Unlike cell surface binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Kallistatin, but not its heparin mutant, was also demonstrated to suppress VEGF-induced proliferation, migration and permeability in endothelial cells [11]. Studies have indicated that LRP binds to a synthetic heparin-mimicking compound on the surface of vascular smooth muscle cells [28] and functions as a heparin-dependent adhesion receptor for connective tissue growth factor in hepatic cells [29]. Therefore, it is likely that kallistatin binds to LRP6 via its heparin-binding site.…”
Section: Discussionmentioning
confidence: 99%
“…Kallistatin, but not its heparin mutant, was also demonstrated to suppress VEGF-induced proliferation, migration and permeability in endothelial cells [11]. Studies have indicated that LRP binds to a synthetic heparin-mimicking compound on the surface of vascular smooth muscle cells [28] and functions as a heparin-dependent adhesion receptor for connective tissue growth factor in hepatic cells [29]. Therefore, it is likely that kallistatin binds to LRP6 via its heparin-binding site.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the authors found that when up to 1 μg/mL of RG-13577 was incubated in the presence of 20 ng/mL of heparin, increased binding of FGF2 to its receptor was observed. Even though RG-13577 has received attention for its inhibitory activity in cells that cause angiogenesis, arteriosclerosis, glomerulosclerosis, and spinal chord inflammation, this last data at lower concentrations suggested that RG-13577 could be further investigated as candidate for regenerative therapy in combination with heparin.…”
Section: Heparin-mimicking Polymersmentioning
confidence: 99%